2014
DOI: 10.1089/ars.2013.5603
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Oxidases: A Perspective on Reactive Oxygen Species Production in Tumor Biology

Abstract: Significance: Reactive oxygen species (ROS) promote genomic instability, altered signal transduction, and an environment that can sustain tumor formation and growth. The NOX family of NADPH oxidases, membranebound epithelial superoxide and hydrogen peroxide producers, plays a critical role in the maintenance of immune function, cell growth, and apoptosis. The impact of NOX enzymes in carcinogenesis is currently being defined and may directly link chronic inflammation and NOX ROS-mediated tumor formation. Recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
147
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(150 citation statements)
references
References 152 publications
(166 reference statements)
1
147
0
2
Order By: Relevance
“…- [111] . Increased ROS generation can induce lipid peroxidation and protein oxidation, hampering normal cellular processes.…”
Section: Generation Of Ros In Biological Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…- [111] . Increased ROS generation can induce lipid peroxidation and protein oxidation, hampering normal cellular processes.…”
Section: Generation Of Ros In Biological Systemsmentioning
confidence: 99%
“…ROS also stimulate the expression of Snail and cause damage to DNA and subsequent genomic instability [128] . Reports have suggested a possible association of Nox and Nox-mediated ROS generation for carcinogenesis [111] . Nox1 is involved in H. pylori-induced gastric cancer and in angiogenic responses for tumour formation [129,130] .…”
Section: Verma S Et Al Mmps In Gastrointestinal Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor-infiltrating immune cells such as macrophages, neutrophils, dendritic cells, and T cells also display NF-kB activation that facilitates IL-6, IL-1, TNFa, and ROS secretion (Karin and Greten, 2005;Inoue et al, 2007). Correspondingly, NOX isoforms have been detected in several solid tumors Meitzler et al, 2014;Höll et al, 2016) and hematopoietic malignancies (Juhasz et al, 2009;Hole et al, 2013), where they modulate protumoral characteristics that resemble the effects of NF-kB (Maraldi et al, 2009;Meitzler et al, 2014;Sanchez-Sanchez et al, 2014;Liu et al, 2015); in fact, it has been shown that NOX isoform induction is at least partially mediated by NF-kB Roy et al, 2015). Moreover, NOX activity and ROS production in macrophages is required for Treg induction (Kraaij et al, 2010), a key population in controlling T cell responses during inflammatory conditions such as cancer.…”
Section: Role Of Proton Channel Hv1 In Immune Cellsmentioning
confidence: 99%
“…Diversas pesquisas com osteossarcoma utilizando terapias alternativas foram investigadas (MEYERS et al, 2008;PILZ et al, 2012;SPINA et al, 2013;LUETKE et al, 2014;KUNDU et al, 2014;ANDERSON, 2016 Estudos recentes descreveram o aumento da expressão de Nox1, Nox2, Nox4 e Nox5 em muitas linhagens células de câncer e em tumores humanos no estágio inicial e tardio, indicando sua importância na progressão do câncer (JUHASZ et al, 2010;MEITZLER et al, 2014;HÖLL et al, 2016). Também foi demonstrado que a perda da expressão de Duox1 em células de câncer de pulmão está fortemente associada com a perda do marcador epitelial E-caderina e que o silenciamento do Duox1 promove a transição de célula epitelial para mesenquimal (EMT), uma importante característica do câncer metastático (LITTLE et al, 2016).…”
Section: Osteossarcomaunclassified